What determines the access to credit by SMEs in Argentina? - Bebczuk, Ricardo Néstor (2004)
This work discusses the determinants of the access to credit for a sample of about 140 Argentine small and medium firms, based on a unique database gathered by the Union Industrial Argentina in 1999. Among other findings, the evidence shows that the acceptance of overdraft lines at high interest rates and very short maturity is an important factor regarding the probability of getting a bank loan, while the availability of collateral does not seem to affect such probability. All in all, the results appear to be consistent with a risk taking behavior by banks in their loan policy toward this set of firms, an observation seemingly at odds with the conservative strategy that presumably banks follow.